A proactive fuzzy-guided link labeling algorithm based on MIH framework in heterogeneous wireless networks - Salih Y.K.; See O.H.; Yussof S.; Iqbal A.; Mohammad Salih S.Q. (Kluwer Academic Publishers, 2023)
Future wireless networks aim to provide a seamless connectivity among different communication networks, while offering a rich range of services with variable bandwidth and quality of service anytime and anywhere. Media independent handover (MIH) represents a successful deployment method towards the integration between heterogeneous wireless networks. It can provide the information about the parameters that affect on the events generation. An efficient system that generates links trigger mechanism will extensively impact the handover performance. This paper proposes a proactive fuzzy-guided algorithm with dynamic links triggering for vertical handover initiation based on the neighbor network information from the information server of MIH. The result shows that the proposed solution can avoid unnecessary handover and service interruption in the heterogeneous wireless network. © 2013 Springer Science+Business Media New York.